A regional perspective on the French 35 hour week policy - Flutter, C (2003)
﻿ In 1998, the French Socialist Government reduced the statutory workweek to 35 hours. This work time reduction policy was implemented in response to the country's chronic unemployment problem, which had seen unemployment average over 10% during the previous decade. The 35 hour week sought to reduce unemployment by spreading the existing stock of jobs more widely and by stimulating job creation. This policy choice was received with considerable scepticism from commentators outside of France. Critics argued that the 35 hour week diverged too greatly from the international orthodoxy of a flexible and deregulated labour market and, given the convergence pressures caused by contemporary globalisation, would reduce French competitiveness. The implication was that governments no longer had the freedom to implement employment policy that diverged from the international norm. In this thesis, I reconsider this argument. I undertake a political economy analysis of the use of work time reduction policy in France from the perspective of the regional labour market of Nord-Pas-de-Calais. In doing so, I focus on the implementation of the 35 hour week policy in this high unemployment region. In addition, I focus on the regional work time reduction policy implemented in Nord-Pas-de-Calais, which predated the national 35 hour week policy and was the source of several of its key features. Thus, I provide a regional perspective on the French 35 hour week policy, an alternative to the 'top down' perspective taken by its critics. Throughout this research, I concentrate on three key issues: (1) the logic of work time reduction policy within the local labour market in France, using Nord-Pas-de-Calais as my case study; (2) the method of policy-making and the importance of geographic scale; and (3) the viability of France's work time reduction policy in the face of globalisation. My aim is to understand the policy process that led to this policy choice, to appreciate how traditions of economic governance influenced its formation and implementation in the local labour market, and to study how these traditions influenced the ability of work time reduction policy to reduce unemployment. I show, first, that French traditions of labour market governance, on which work time reduction policy is based, continue to have meaning in the local labour market, with the public continuing to demand policy consistent with its ideals. Second, I show that scale contributes to policy outcomes and policy innovation, suggesting the importance of geographic factors in the policy, process, such as the spatial match between the policy and policy problem, the transfer of policy between scales, and issues such as proximity and homogeneity. Third, I show that the success of work time reduction policy is largely dependent upon socially determined factors including effective negotiation, preferences between work and leisure, and empathy for the unemployed. Fourth, I show that the 35 hour week policy was not incompatible with international demands for labour market flexibility because it provided significant scope for productivity gains via its design and increased flexibility in the use of work time, albeit within constraints. Therefore, by examining the making and implementation of work time reduction policy in France from a regional perspective, I show that while globalisation places genuine exogenous constraints on the policy choices of government, there nonetheless remains considerable scope within these constraints, especially when implementing policy that is compatible with traditions of governance that continue to resonate in the local labour market.